2016
DOI: 10.1002/anie.201607988
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free meta‐Selective Alkyne Oxyarylation with Pyridine N‐Oxides: Rapid Assembly of Metyrapone Analogues

Abstract: An efficient metal-free oxyarylation of electron-poor alkynes with pyridine N-oxides has been developed. This transformation affords meta-substituted pyridines analogous to the drug metyrapone in high regioselectivities. Density functional theory (DFT) calculations provided important insight into the mechanism. Evaluation of the inhibitory properties revealed the most active CYP11B1 inhibitor of these derivatives, with two-digit nanomolar inhibitory activity akin to that of metyrapone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 63 publications
(19 reference statements)
0
21
0
2
Order By: Relevance
“…Other examples comprise cycloaddition reactions of ynones, diynes and enynones with quinoline and isoquinoline N ‐oxides, and meta ‐selective alkyne oxyarylation with pyridine N ‐oxides …”
Section: Oxygenation Of Unsaturated Bondsmentioning
confidence: 99%
“…Other examples comprise cycloaddition reactions of ynones, diynes and enynones with quinoline and isoquinoline N ‐oxides, and meta ‐selective alkyne oxyarylation with pyridine N ‐oxides …”
Section: Oxygenation Of Unsaturated Bondsmentioning
confidence: 99%
“…We then investigated other non-noble metals (Table 1 , entries 2−6), and were pleased to find that Cu(CH 3 CN) 4 PF 6 catalyzed the oxidative cyclization to produce the desired 2a in 41% yield (Table 1 , entry 6). Of note, rhodium (Table 1 , entry 7) 35 and Brønsted acids 56 59 such as TsOH and TfOH were not effective in promoting this reaction (for more details see Supplementary Table 1 ). Interestingly, pyrrolo[2,3- b ]indole 3a was obtained as the main product in the presence of typical gold catalysts such as Ph 3 PAuNTf 2 and IPrAuNTf 2 (Table 1 , entries 8 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…[12] Primary and secondary aniline derivatives are also wellknown to act as ortho-directing groups for metal-catalyzed C À Hf unctionalization (Scheme 1b). [14] Additionally,w ea nd others [15] have observed that the addition of pyridine N-oxides to keteniminium intermediates may lead to the formation of an electrophilic enolonium-like species that is prone to interception by appropriate nucleophiles (Scheme 1c,b ottom reaction). [14] Additionally,w ea nd others [15] have observed that the addition of pyridine N-oxides to keteniminium intermediates may lead to the formation of an electrophilic enolonium-like species that is prone to interception by appropriate nucleophiles (Scheme 1c,b ottom reaction).…”
mentioning
confidence: 99%